International Society of Sports Nutrition position stand: energy drinks - Campbell, B.; Wilborn, C.; La Bounty, P.; Taylor, L.; Nelson, M. T.; Greenwood, M.; Ziegenfuss, T. N.; Lopez, H. L.; Hoffman, J. R.; Stout, J. R.; Schmitz, S.; Collins, R.; et al. (Journal of the International Society of Sports Nutrition, 2013)
Position Statement: The International Society of Sports Nutrition (ISSN) bases the following position stand on a critical analysis of the literature on the safety and efficacy of the use of energy drinks (ED) or energy shots (ES). The ISSN has concluded the following. 1. Although ED and ES contain a number of nutrients that are purported to affect mental and/or physical performance, the primary ergogenic nutrients in most ED and ES appear to be carbohydrate and/or caffeine. 2. The ergogenic value of caffeine on mental and physical performance has been well-established but the potential additive benefits of other nutrients contained in ED and ES remains to be determined. 3. Consuming ED 10-60 minutes before exercise can improve mental focus, alertness, anaerobic performance, and/or endurance performance. 4. Many ED and ES contain numerous ingredients; these products in particular merit further study to demonstrate their safety and potential effects on physical and mental performance. 5. There is some limited evidence that consumption of low-calorie ED during training and/or weight loss trials may provide ergogenic benefit and/or promote a small amount of additional fat loss. However, ingestion of higher calorie ED may promote weight gain if the energy intake from consumption of ED is not carefully considered as part of the total daily energy intake. 6. Athletes should consider the impact of ingesting high glycemic load carbohydrates on metabolic health, blood glucose and insulin levels, as well as the effects of caffeine and other stimulants on motor skill performance. 7. Children and adolescents should only consider use of ED or ES with parental approval after consideration of the amount of carbohydrate, caffeine, and other nutrients contained in the ED or ES and a thorough understanding of the potential side effects. 8. Indiscriminant use of ED or ES, especially if more than one serving per day is consumed, may lead to adverse events and harmful side effects. 9. Diabetics and individuals with pre-existing cardiovascular, metabolic, hepatorenal, and neurologic disease who are taking medications that may be affected by high glycemic load foods, caffeine, and/or other stimulants should avoid use of ED and/or ES unless approved by their physician.